Teachers’ perspectives of assessment and alternative assessment in the classroom - Sulaiman, Tajularipin; Abdul Rahim, Suzieleez Syrene; Abdullah, Muhammad Nazrul Hakim; Omar, Rosmaria (International Journal of Innovative Technology and Exploring Engineering, 2019)
This study aims to explore teachers’ perspectives of the elements in assessment, choice of the types of assessment and perspectives of alternative assessment. The study was a case study involving seven in-service secondary school teachers who were interviewed. The findings indicate that respondents develop questions based on bloom’s taxonomy and higher order thinking. Formative and summative assessment are used to create a more comprehensive classroom assessment. Also, the respondents view alternative assessment as consisting of various techniques.